Efficacy and Safety of Anti-Interleukin-20 Monoclonal Antibody in Patients With Rheumatoid Arthritis: A Randomized Phase IIa Trial - Šenolt, Ladislav; Leszczynski, Piotr; Dokoupilová, Eva; Göthberg, Marie; Valencia, Xavier; Hansen, Brian Bekker; Cañete, Juan D (Arthritis & rheumatology (Hoboken, N.J.), 2015)
OBJECTIVE: Interleukin-20 (IL-20) is implicated in the pathogenesis of rheumatoid arthritis (RA). The efficacy, safety, and tolerability of NNC0109-0012, a selective anti-IL-20 recombinant human monoclonal antibody (mAb), were assessed in patients with active RA who had an inadequate response to methotrexate therapy. METHODS: Sixty-seven patients with RA were enrolled and randomized (2:1) to receive NNC0109-0012 (3 mg/kg per week, subcutaneously) or placebo in a phase IIa, double-blind, 12-week trial with a 13-week followup. The primary end point was change in the Disease Activity Score in 28 joints based on C-reactive protein level (DAS28-CRP) from baseline to week 12. RESULTS: In patients treated with NNC0109-0012, the primary end point, improvement in the DAS28-CRP at week 12, was achieved (estimated difference -0.88; P = 0.02), with significant improvement starting at week 1. A greater response was observed in seropositive patients (estimated difference -1.66; P < 0.001), which was sustained through 13 weeks of followup, whereas no improvement was noted in patients with seronegative RA. A significant proportion of patients with seropositive RA receiving NNC0109-0012, compared to those receiving placebo, achieved treatment responses according to the American College of Rheumatology 20% (ACR20) (59% versus 21%), ACR50 (48% versus 14%), and ACR70 (35% versus 0%) levels of improvement, and showed greater improvements in the Health Assessment Questionnaire disability index (P = 0.047). The most frequent adverse events reported with NNC0109-0012 were injection site reactions and infections (e.g., herpes, nasopharyngitis, respiratory, and urinary). No serious infections or discontinuations associated with NNC0109-0012 were observed. CONCLUSION: In this phase IIa trial, treatment with NNC0109-0012 (anti-IL-20 mAb) was effective in patients with seropositive RA as early as week 1, with further improvements to week 12. No safety or tolerability concerns were identified with weekly NNC0109-0012 administration.
Keywords: Female; lidé středního věku; Antirheumatic Agents; Rheumatoid Factor; revmatoidní artritida; infekce dýchací soustavy; Antibodies, Monoclonal, Humanized; Adolescent; Respiratory Tract Infections; Herpes Simplex; mužské pohlaví; interleukiny; Urinary Tract Infections; Autoantibodies; mladý dospělý; Arthritis, Rheumatoid; neutralizující protilátky; Humans; dospělí; autoprotilátky; revmatoidní faktor; Peptides, Cyclic; nazofaryngitida; humanizované monoklonální protilátky; lidé; Male; široce neutralizující protilátky; dvojitá slepá metoda; Broadly Neutralizing Antibodies; Middle Aged; senioři; C-Reactive Protein; monoklonální protilátky; herpes simplex; Antibodies, Monoclonal; Nasopharyngitis; Treatment Outcome; ženské pohlaví; Aged; cyklické peptidy; Double-Blind Method; Young Adult; Interleukins; Adult; infekce močového ústrojí; Antibodies, Neutralizing; antirevmatika; mladiství; výsledek terapie; C-reaktivní protein